2020
DOI: 10.1002/rrq.294
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Professional Development Model for Writing as a Digital, Participatory Process

Abstract: In this formative experiment, the authors focused on developing professional development for upper elementary school teachers and investigating how it was integrated into teachers’ instruction to improve their ability to make writing a more digital, participatory process. Theoretical perspectives pertaining to technology use in education specify that this instruction should emphasize students creating rather than consuming information from media sources and that this creation process should be social. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…This study explored the instructional moves in support of lateral reading. Specifically, we wanted to identify the elements that enhance progress to the instructional goal of supporting students’ complex, hierarchical thinking during digital source evaluation (Colwell et al, 2013; Howell et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study explored the instructional moves in support of lateral reading. Specifically, we wanted to identify the elements that enhance progress to the instructional goal of supporting students’ complex, hierarchical thinking during digital source evaluation (Colwell et al, 2013; Howell et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…While our previous research has shown that lateral reading instruction as a source evaluation strategy increases learners’ skeptical stances (Walsh‐Moorman & Pytash, 2021; Walsh‐Moorman et al, 2020), we have also found that students’ reasoning remains limited due to poor related skills, including effective web‐based searching or the ability to synthesize information from multiple online texts. This study was designed as a formative design study (Howell et al, 2020; Reinking & Bradley, 2008) to identify instructional moves targeting the pedagogical goal of guiding students’ effective use of lateral reading for digital source evaluation. It was shaped by these research questions: What instructional moves support learners' abilities to strategically evaluate digital sources through lateral reading? What evidence is there that comprehensive lateral reading instruction can support students’ critical thinking, supporting them to consider multiple factors when evaluating online sources for potential bias? …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that language teachers learn better by testing and refining their knowledge in context through collaborative inquiry, which is a process where teachers work in groups to explore questions of teaching and learning that they identify as significant (Burns, 1999). However, given the contextual barriers such as limited time and the exam‐oriented culture, such inquiry is rarely included in teachers’ professional development (Howell, Perez, & Abraham, 2021). To facilitate teacher inquiry, we used the gradual release of responsibility model that supports teachers’ moving from guided instruction to collaborative learning and independent work (Howell et al., 2021).…”
Section: Teacher Inquirymentioning
confidence: 99%
“…However, given the contextual barriers such as limited time and the exam‐oriented culture, such inquiry is rarely included in teachers’ professional development (Howell, Perez, & Abraham, 2021). To facilitate teacher inquiry, we used the gradual release of responsibility model that supports teachers’ moving from guided instruction to collaborative learning and independent work (Howell et al., 2021). This model includes three main steps, ranging from “We do it” (guided instruction), to “You do it together” (collaborative learning) and “You do it alone” (independent practice) (Fisher, 2008, p. 4).…”
Section: Teacher Inquirymentioning
confidence: 99%